KLF5 promotes esophageal squamous cell carcinoma radioresistance by targeting the Keap1-Nrf2 pathway - Yang Wang; Yue-ying Yang; Abulajiang Kamili; Dilimulati Aishanjiang; Yi Liu (Discover Oncology)
Abstract Objective Esophageal squamous cell carcinoma (ESCC) has high morbidity and mortality in developing countries. The purpose of this article is to study the mechanism of KLF5's effect on ESCC radiosensitivity. Methods WGCNA gene expression profiling identified core genes associated with ESCC radiosensitivity. KLF5 expression was detected by RT-qPCR. The effects of overexpression or downregulation of KLF5 on anti-irradiated cells' proliferation, migration, invasion, and apoptotic activity were studied through colony formation assay, Transwell assay, and flow cytometry. Western blot can detect the activity of Nrf2 signaling pathway in cells and tissues. The enrichment of KLF5 at the Keap1 promoter was analyzed by ChIP-base, and the binding of KLF5 to Keap1 was analyzed by ChIP and dual-luciferase. They then injected ESCC cells into mice and used radiation to monitor tumor progression. Results KLF5 is a core gene in ESCC and is significantly associated with radiosensitivity. KLF5 expression is upregulated in drug-resistant ESCC cells. Overexpression of KLF5 significantly increased cell viability and attenuated cellular responses to radiation. KLF5 knockdown reduces radioresistance. After KLF5 overexpression, the Nrf2 signaling pathway was significantly up-regulated, and after KLF5 was up-regulated, the Keap1 signaling pathway was down-regulated. KLF5 inhibits the transcriptional activity of Keap1. Upregulation of Keap1 inhibits the effect of KLF5 overexpression on radioresistance of ESCC cells. KLF5/Keap1 regulates the effects of ESCC on in vivo radiotherapy. Conclusion KLF5 promotes ESCC radioresistance by inhibiting Keap1 transcription and activating the Nrf2 pathway.